(untitled) (Lex localis - Journal of Local Self-Government, 2025)
A Turning point in India’s democratic history occurred in 1992 with the 73rd Constitutional Amendment, which established Panchayati Raj Institutions (PRIs) and mandated the reservation of one-third of seats for women. This reform aimed to enhance women’s representation and empower them in grassroots governance. Over the past three decades, women now comprise about 46% of elected representatives in PRIs, positioning India as a global leader in gender-inclusive local governance. However, it is crucial to recognize that women’s participation is influenced by local social, economic, and political dynamics, necessitating a deeper understanding of these interconnected factors in PRIs. Notwithstanding these developments, there are still important concerns regarding the degree to which descriptive representation results in meaningful empowerment. Although there is evidence that female leaders have had a good impact on government objectives in sectors including sanitation, water, health, and education, obstacles still stand in the way of their full decision-making ability. Their autonomy and efficacy are nonetheless hampered by entrenched patriarchal norms, the use of proxy leadership, a lack of training opportunities, rotating seat reservations and a lack of digital literacy. The contribution of PRIs to women’s empowerment in rural India is critically examined in this review study. It summarizes the body of research, assesses societal and institutional obstacles and examines the revolutionary possibilities of grassroots women’s leadership. The study emphasizes that although PRIs have created previously unheard-of opportunities for women to participate, empowerment is still unequal and dependent on structural changes, capacity-building, and encouraging community settings. The paper adds to larger discussions on decentralization, gender equality, and inclusive governance by examining both successes and limitations.